Ca2+/Calcineurin-Dependent Inactivation of Neuronal L-Type Ca2+ Channels Requires Priming by AKAP-Anchored Protein Kinase A - Philip J. Dittmer (Cell Reports, 2014)
Within neurons, Ca2+-dependent inactivation (CDI) of voltage-gated L-type Ca2+ channels shapes cytoplasmic Ca2+ signals. CDI is initiated by Ca2+ binding to channel-associated calmodulin and subsequent Ca2+/calmodulin activation of the Ca2+-dependent phosphatase, calcineurin (CaN), which is targeted to L channels by the A-kinase-anchoring protein AKAP79/150. Here, we report that CDI of neuronal L channels was abolished by inhibition of PKA activity or PKA anchoring to AKAP79/150 and that CDI was also suppressed by stimulation of PKA activity. Although CDI was reduced by positive or negative manipulation of PKA, interference with PKA anchoring or activity lowered Ca2+ current density whereas stimulation of PKA activity elevated it. In contrast, inhibition of CaN reduced CDI but had no effect on current density. These results suggest a model wherein PKA-dependent phosphorylation enhances neuronal L current, thereby priming channels to undergo CDI, and Ca2+/calmodulin-activated CaN actuates CDI by reversing PKA-mediated enhancement of channel activity.